ALEXEY RESHCHIKOV & ILARI EERIKKI SÄÄKSJÄRVI (2015) Seven new species of the genus Physotarsus Townes 1966 (Hymenoptera, Ichneumonidae) from South America. Zootaxa, 3972(1): 026–042. - Reshchikov, Alexey; Sääksjärvi, Ilari Eerikki (Zootaxa, 2016)
N/A